2018
DOI: 10.3390/f9030130
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Potential Fire Severity Using Vegetation, Topography and Surface Moisture Availability in a Eurasian Boreal Forest Landscape

Abstract: Severity of wildfires is a critical component of the fire regime and plays an important role in determining forest ecosystem response to fire disturbance. Predicting spatial distribution of potential fire severity can be valuable in guiding fire and fuel management planning. Spatial controls on fire severity patterns have attracted growing interest, but few studies have attempted to predict potential fire severity in fire-prone Eurasian boreal forests. Furthermore, the influences of fire weather variation on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 100 publications
3
28
0
Order By: Relevance
“…The degree of fire-induced ecological change, or fire severity, has been the focus of countless studies across the globe [1][2][3][4][5]. These studies often rely on gridded metrics that use pre-and post-fire imagery to estimate the amount of fire-induced change; the most common metrics are the delta normalized burn ratio (dNBR) [6], the relativized delta normalized burn ratio (RdNBR) [7], and the relativized burn ratio (RBR) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of fire-induced ecological change, or fire severity, has been the focus of countless studies across the globe [1][2][3][4][5]. These studies often rely on gridded metrics that use pre-and post-fire imagery to estimate the amount of fire-induced change; the most common metrics are the delta normalized burn ratio (dNBR) [6], the relativized delta normalized burn ratio (RdNBR) [7], and the relativized burn ratio (RBR) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The fire severity datasets produced by the MTBS program have clearly advanced wildland fire research in the US. Although some studies involving the trends, drivers, and distribution of satellite-inferred fire severity are evident outside of the US [4,5,15,29,30], the number and breadth of such studies are relatively scarce and restricted compared to those conducted in the US. We suggest that, if spatially and temporally comprehensive satellite-inferred severity metrics were more widely available in other countries or regions, opportunities for fire severity monitoring and research would increase substantially.…”
Section: Introductionmentioning
confidence: 99%
“…) we studied was ignited by lightning on 17 June 2000 and lasted for seven days [45]. It burned an area approximately 7735 ha, most of which was moderate-high severity with high tree mortality rates [26,39].…”
Section: Study Areamentioning
confidence: 99%
“…A strict ban on logging of natural forests has been enforced across the Great Xing'an Mountains since April 2014, thus historical fires in the nature reserve will provide valuable insight for understanding how resilient this forest is in responding to wildfire and for refining post-fire management practices. The particular fire (Lat/Lon: 122°50′E, 51°53′N) we studied was ignited by lightning on 17 June 2000 and lasted for seven days [45]. It burned an area approximately 7735 ha, most of which was moderate-high severity with high tree mortality rates [26,39].…”
Section: Study Areamentioning
confidence: 99%
“…However, recent studies have found that these interactions and the potential heterogeneity across landscapes could be modified by disturbances [9][10][11]. Wildfire is one of the most important natural ecological disturbance agents in forest ecosystems, is characterized by variations in fire severity and frequency [12,13], and therefore produces spatial and temporal variations in ecological systems. Fire frequency and severity have been predicted to increase under a warming climate [14]; thus, understanding changes in patterns of post-fire soil resources and plants across space is necessary to better understand the ecological effects of fires in fire-prone ecosystems.…”
Section: Introductionmentioning
confidence: 99%